Global nonexistence of solutions to system of Klein-Gordon equations with degenerate damping and strong source terms in viscoelasticity - YAZID, Fares; OUCHENANE, Djamel; ZENNIR, Khaled (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
In this paper, we consider a system of nonlinear viscoelastic wave equations with degenerate damping and source terms. We prove, with positive initial energy, the global nonexistence of solution by concavity method. Mathematics Subject Classification (2010): 35L70, 35B40, 93D20. Received 5 November 2019; Accepted 18 March 2020.